2006
DOI: 10.1007/s11141-006-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the vertical advection on the nonlinear dynamic properties of the upper-mesosphere photochemistry

Abstract: 551.510We study the influence of the vertical advection on the behavior of the mesospheric photochemical system (altitudes from 80 to 90 km), which is initially in the regime of a nonlinear (subharmonic) response to diurnal variations in solar radiation. It is shown that allowance for the atmospheric transport significantly modifies the nonlinear dynamic properties of this system and, depending on the value and speed direction of the mean vertical wind, can lead to either a suppression of nonlinear oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The other studies (e.g., Kulikov, 2004, 2007; Kulikov & Feigin, 2004, 2005; Kulikov & Gashturi, 2006; Sonnemann, 2001; Sonnemann et al, 1999; Sonnemann & Feigin, 1999; Sonnemann & Grygalashvyly, 2005) concerned the influence of different types of mesospheric transport (diffusion and winds in the vertical and horizontal directions and quasi‐2‐day atmospheric waves). In particular, Sonnemann and Feigin (1999) and Sonnemann et al (1999) analyzed the influence of the vertical eddy diffusion and found that in most cases only the first nontrivial mode of behavior (oscillations with periods of 2 days) can survive at the real values of the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The other studies (e.g., Kulikov, 2004, 2007; Kulikov & Feigin, 2004, 2005; Kulikov & Gashturi, 2006; Sonnemann, 2001; Sonnemann et al, 1999; Sonnemann & Feigin, 1999; Sonnemann & Grygalashvyly, 2005) concerned the influence of different types of mesospheric transport (diffusion and winds in the vertical and horizontal directions and quasi‐2‐day atmospheric waves). In particular, Sonnemann and Feigin (1999) and Sonnemann et al (1999) analyzed the influence of the vertical eddy diffusion and found that in most cases only the first nontrivial mode of behavior (oscillations with periods of 2 days) can survive at the real values of the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of the nonlinear response of mesospheric photochemistry (Sonnemann et al, 1999;Sonnemann and Feigin, 1999;Sonnemann, 2001;Feigin, 2004, 2005;Kulikov, , 2007Sonnemann and Grygalashvyly, 2005;Kulikov and Gashturi, 2006) revealed that behavior of the concentrations of minor gas constituents may be simpler…”
Section: Introductionmentioning
confidence: 99%